coughsyrup78
New member
- Joined
- May 31, 2011
- Messages
- 15
I'm having trouble factoring this polynomial.
12x2 - 25xy + 7y2
My work:
12x2 - 25xy + 7y2 =
12x2 - 28xy + 3xy + 7y2 =
(12x2 - 28xy) + (3xy + 7y2)=
3x(4x - 7y) - y(3x - 7y) =
I can't continue any further because the (3x - 7y) should be (4x - 7y).
I think I might be grouping incorrectly. I tried rearranging the terms different ways and I still can't get it to work.
Thanks in advance for your help.
12x2 - 25xy + 7y2
My work:
12x2 - 25xy + 7y2 =
12x2 - 28xy + 3xy + 7y2 =
(12x2 - 28xy) + (3xy + 7y2)=
3x(4x - 7y) - y(3x - 7y) =
I can't continue any further because the (3x - 7y) should be (4x - 7y).
I think I might be grouping incorrectly. I tried rearranging the terms different ways and I still can't get it to work.
Thanks in advance for your help.